Implementation and Control of A Liquid Level Model - Huynh, Minh Vũ; Duong, Khánh Sơn; Tran, Minh Phát (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Control engineering is an interdisciplinary field requiring knowledge on math and physics, circuits, sensors, actuator, and microcontrollers. It also provides users experiences in testing, simulation and real-time implementation. This paper aims to build and control a liquid level stability model, which can be used to test different control algorithms. The proposed solution is to build low-cost hardware based on Arduino Mega and the PID controller has been built on MATALB/Simulink software for stable control of liquid level. Experimental results on the PID controller shows that the response of the model has suitable setting time, negligible overshoot and small steady-state error. With the above results, the model completely meets the requirements of practice and experiment on system control.